CAUSES, FORMS, VICTIMS OF VIOLENCE AND WAYS TO COMBAT IT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Through this article, I will explain in detail what violence is, the mental state of people who commit this crime, the reasons for committing such a crime, the victims of this deplorable crime, and their subsequent lives. Why is this crime committed almost exclusively by girls? Today, the situations that happened to young men several years ago are revealed in front of the public through social networks. So, what is the reason for this? You can learn more about why violence against men is now coming to light, what punishments are used today for the perpetrators of this crime, and what types of violent crimes exist.